Variation in injury risk over the course of a two-day youth club soccer tournament. Issue 4 (3rd August 2009) - Rosenbaum, D A; Silvis, M L; Williams, J E; Davis, S W
Abstract : Athletic injury risk in youth is known to be greater in organised sport, higher levels of competition, games, and tournaments, yet young athletes are often expected to participate in tournaments that involve multiple matches per day on consecutive days. In 2006 and 2008 injury rates were observed during a club youth soccer tournament that involved athletes aged 9–18 years playing three to four matches over two consecutive days, to determine if injury risk varied over the course of the event. The injury rate for day 1 was 7.91/1000 hours with a mean severity of 3.5 days missed versus a day 2 rate of 6.75 and severity of 2.3. The rate and severity for the first game in a day were 7.13 and 3.5 respectively compared to 7.9 and 2.5 for game 2. Further research is needed to determine if a high density match schedule increases injury risk for youth soccer players.